Natural co-occurrence of mycotoxins in wheat grains from Italy and Syria - Alkadri, D; Rubert, J; Prodi, A; Pisi, A; Mañes, J; Soler, C (Food chemistry, 2014)
This article describes the application of an analytical method for the detection of 25 mycotoxins in wheat grain based on simultaneous extraction using matrix solid-phase dispersion (MSPD) followed by liquid chromatography coupled to tandem mass spectrometry, a hybrid triple quadrupole-linear ion trap mass spectrometer (QTrap®). Information Dependent Acquisition (IDA), an extra confirmation tool for samples that contain the target mycotoxins, was used. The analysis of 40 Syrian and 46 Italian wheat grain samples interestingly showed that Syrian samples were mainly contaminated with ochratoxin A and aflatoxins, whereas Italian samples with deoxynivalenol and 15-acetyldeoxynivalenol. Emerging Fusarium mycotoxins were predominant in Italian samples compared to the Syrian. Among the analysed samples, only one was found containing zeralenone with level above the maximum European recommended concentration (100 ppb). These results confirm that climatic differences between Syria and Italy, both in Mediterranean basin, play a key role in the diversity of fungal genera and mycotoxins in wheat grains.
Keywords: Aflatoxins; Sýrie; Chromatography, Liquid; Syria; Triticum; Italy; Itálie; aflatoxiny; Liquid chromatography–mass spectrometry; plynová chromatografie s hmotnostně spektrometrickou detekcí; Mycotoxins; EDI; Co-occurrence; Gas Chromatography-Mass Spectrometry; pšenice; mykotoxiny; Wheat grain; chromatografie kapalinová